1993
DOI: 10.1007/bf00401138
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus due to viruses ? some recent developments

Abstract: Many different viruses belonging to several genera have the potential to damage beta cells. The mechanisms they employ are varied, and infection may result in either a direct destruction of islets and rapid insulin deficiency, or in a more gradual loss of functioning islets with the onset of diabetes many years later. Several case histories involving extensive cytolysis of beta cells can be directly linked to viral infection, whilst an example of diabetes occurring many years after viral infection is found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
85
2
6

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(103 citation statements)
references
References 102 publications
3
85
2
6
Order By: Relevance
“…According to our results, echovirus 16 could be involved in an autoimmune induction against beta-cell antigens, due to the fact that the presence of neutralizing antibodies to echovirus 16 was associated with the appearance of or increases in islet-associated antibody concentrations. This suggests that such enterovirus could be capable of inducing the destruction of pancreatic beta cells by releasing self cytoplasmatic antigens, or indirectly generating cytokine production [7,11,14,15,35,36], all of which might trigger Type 1 diabetes of autoimmune origin in subjects with susceptibility genes [8,10,11,15]. In addition, molecular mimicry can also be an explanation for this association [7,11,14,20,35].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to our results, echovirus 16 could be involved in an autoimmune induction against beta-cell antigens, due to the fact that the presence of neutralizing antibodies to echovirus 16 was associated with the appearance of or increases in islet-associated antibody concentrations. This suggests that such enterovirus could be capable of inducing the destruction of pancreatic beta cells by releasing self cytoplasmatic antigens, or indirectly generating cytokine production [7,11,14,15,35,36], all of which might trigger Type 1 diabetes of autoimmune origin in subjects with susceptibility genes [8,10,11,15]. In addition, molecular mimicry can also be an explanation for this association [7,11,14,20,35].…”
Section: Discussionmentioning
confidence: 99%
“…Among such serotypes, CVB4 and CVB5 have most often been connected to the pathogenesis of Type 1 diabetes, although other studies have reported the participation of other enterovirus serotypes, such as coxsackie A and echoviruses (EV4, EV6 and EV9) [11,14,16,17,18,19,33,34]. Echovirus 16 could be another serotype to be included in the list of enteroviruses related to Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations